Direct observation of ultrafast non-thermal melting by ultrafast x-ray diffraction - Siders, C; Cavalleri, A; Sokolowski-Tinten, K; Toth, C; Guo, T; Kammler, M; von Hoegen, M; Wilson, K; von der Linde, D; Barty, C (2001)
Ultrafast nonthermal melting of femtosecond laser-irradiated germanium was observed directly for the first time using sub-picosecond, 1.54-angstrom x-ray diffraction. Such measurements allow the study of transient atomic motion fundamental to many processes in physics, chemistry, and biology.